2019
DOI: 10.3390/cancers11010039
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Tumor-Infiltrating Lymphocytes and Neutrophils on Survival of Patients with Upfront Resection of Pancreatic Cancer

Abstract: In patients with pancreatic ductal adenocarcinoma (PDAC), the tumor microenvironment consists of cellular and stromal components that influence prognosis. Hence, tumor-infiltrating lymphocytes (TILs) may predict prognosis more precisely than conventional staging systems. Studies on the impact of TILs are heterogeneous and further research is needed. Therefore, this study aims to point out the importance of peritumoral TILs, tumor-infiltrating neutrophils (TINs), and immune subtype classification in PDAC. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 73 publications
7
68
0
Order By: Relevance
“…Several studies on cohorts from 86 to 214 patients with pancreatic cancer have, in contrast, suggested an association between the fraction of CD8 positive lymphocytes or neutrophils with tumor aggressiveness or clinical outcome of pancreatic cancer. [66][67][68] However, spatial variance of CD8-positive cells-typically between central and peripheral tumor areas-is quite prevalent in pancreatic cancer and may confound analyses when information on the precise localization of the analyzed tumor area is not available. 66 TMA-based studies-at least when TMA construction was not focused on tumor compartments as in our study-may underrepresent the invasive margin that has been shown to confer a prognostic role for CD8-positive cells in pancreatic cancer in particular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on cohorts from 86 to 214 patients with pancreatic cancer have, in contrast, suggested an association between the fraction of CD8 positive lymphocytes or neutrophils with tumor aggressiveness or clinical outcome of pancreatic cancer. [66][67][68] However, spatial variance of CD8-positive cells-typically between central and peripheral tumor areas-is quite prevalent in pancreatic cancer and may confound analyses when information on the precise localization of the analyzed tumor area is not available. 66 TMA-based studies-at least when TMA construction was not focused on tumor compartments as in our study-may underrepresent the invasive margin that has been shown to confer a prognostic role for CD8-positive cells in pancreatic cancer in particular.…”
Section: Discussionmentioning
confidence: 99%
“…66 TMA-based studies-at least when TMA construction was not focused on tumor compartments as in our study-may underrepresent the invasive margin that has been shown to confer a prognostic role for CD8-positive cells in pancreatic cancer in particular. 68 Furthermore, pancreatic cancer possess a unique microenvironment characterized by a dense desmoplastic stromal reaction that may enhance regional variability of lymphocytic density. 69 For instance, CD8-positive cells at the invasive margin were significantly associated with overall survival in contrast to the tumor core.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple reports indicate α E (CD103)β 7 interaction with E-cadherin expressed by tumor cells promotes cytolytic T cell activity against different type of tumors such as lung [136] and pancreatic cancer [137]. These data may provide the biological explanation of several clinical data showing that high infiltration of CD8 + lymphocytes correlates with an improved survival in pancreatic cancer patients [138][139][140]. Moreover, it should be noted that CD103 marks also a particular subpopulation of DCs characterized by several functions (i.e., induction of regulatory T cells to maintain tolerance and antigen cross-presentation to CD8 + T cells), playing an important role in immune defense [141][142][143].…”
Section: E-cadherin and The Immune Systemmentioning
confidence: 88%
“…Although not specifically mentioned, it is plausible to hypothesize the involvement of E-cadherin in the generation of MTFs. Second, PDAC is often characterized by lack of infiltration of CD8 + T lymphocytes [152] and, indeed, T cell infiltration is associated with PDAC patient survival [138][139][140]. Different factors can concur in limiting T cell trafficking in the tumor bed and macrophages are one of them [153][154][155].…”
Section: E-cadherin and The Immune Systemmentioning
confidence: 99%
“…Macrophages cells as the second proportion (13%) ( Table 1) The prognostic importance of immune cell infiltration for various solid tumor types has been determined [35][36][37]. In univariate and multivariate Cox analysis, only B cell memory was significantly correlated with RFS.…”
Section: Discussionmentioning
confidence: 99%